130 SEVERITY OF ANASTOMOTIC LEAKAGE AFTER DIFFERENT TYPES OF ESOPHAGECTOMY: A NATIONWIDE COHORT STUDY. (17th September 2021) - Verstegen, Moniek; Slaman, Annelijn; Klarenbeek, Bastiaan; Berge Henegouwen, Mark; Gisbertz, Suzanne; Rosman, Camiel; van Workum, Frans
Abstract: : Orringer, McKeown and Ivor Lewis esophagectomy are the most commonly performed procedures for esophageal and gastro-esophageal junction cancer. Anastomotic leakage remains a major problem after all types of esophagectomy and it is currently unknown whether anastomotic leakage severity is different between the types of esophagectomy. The aim of this study was to investigate the relationship between surgical techniques and the severity of anastomotic leakage in patients after Orringer esophagectomy, McKeown esophagectomy or Ivor Lewis esophagectomy. Methods: All esophageal and gastro-esophageal junction cancer patients with anastomotic leakage after Orringer, McKeown or Ivor Lewis esophagectomy between 2011 and 2019 were selected from the Dutch Upper Gastrointestinal Cancer Audit (DUCA). The primary outcome parameter was a composite endpoint of reoperation, intensive care unit (ICU) readmission and 30-day/in-hospital mortality. Secondary outcome parameters included postoperative complications, re-intervention rate, ICU and hospital length of stay. Results: Data from 1034 patients with anastomotic leakage after Orringer (n = 287), McKeown (n = 397) and Ivor Lewis esophagectomy (n = 346) were evaluated. The primary endpoint occurred in 36.3% of patients with anastomotic leakage after Orringer esophagectomy, in 55.4% of patients with anastomotic leakage after McKeown esophagectomy and in 61.2% of patients with anastomotic leakage after Ivor Lewis esophagectomy (p < 0.001). When adjusting for potential confounding variables, the sequelae of anastomotic leakage after Orringer and McKeown esophagectomy remained less severe compared to anastomotic leakage after Ivor Lewis esophagectomy (OR 0.28, 95% CI 0.20–0.41, p < 0.001 and OR 0.71, 95% CI 0.52–0.97, p = 0.031, respectively). Conclusion: Consequences of anastomotic leakage are most severe after Ivor Lewis esophagectomy, moderately severe after McKeown esophagectomy and least severe after Orringer esophagectomy. This study demonstrated that not only the incidence, but also the severity of anastomotic leakage should be considered in current clinical practice and in studies that compare leakage rates between different surgical techniques of esophagectomy.